Education and coronary heart disease: mendelian randomisation study. (30th August 2017) - Tillmann, Taavi; Vaucher, Julien; Okbay, Aysu; Pikhart, Hynek; Peasey, Anne; Kubinova, Ruzena; Pajak, Andrzej; Tamosiunas, Abdonas; Malyutina, Sofia; Hartwig, Fernando Pires; Fischer, Krista; Veronesi, Giovanni; et al.
Abstract : Objective  To determine whether educational attainment is a causal risk factor in the development of coronary heart disease. Design  Mendelian randomisation study, using genetic data as proxies for education to minimise confounding. Setting  The main analysis used genetic data from two large consortia (CARDIoGRAMplusC4D and SSGAC), comprising 112 studies from predominantly high income countries. Findings from mendelian randomisation analyses were then compared against results from traditional observational studies (164 170 participants). Finally, genetic data from six additional consortia were analysed to investigate whether longer education can causally alter the common cardiovascular risk factors. Participants  The main analysis was of 543 733 men and women (from CARDIoGRAMplusC4D and SSGAC), predominantly of European origin. Exposure  A one standard deviation increase in the genetic predisposition towards higher education (3.6 years of additional schooling), measured by 162 genetic variants that have been previously associated with education. Main outcome measure  Combined fatal and non-fatal coronary heart disease (63 746 events in CARDIoGRAMplusC4D). Results  Genetic predisposition towards 3.6 years of additional education was associated with a one third lower risk of coronary heart disease (odds ratio 0.67, 95% confidence interval 0.59 to 0.77; P=3×10 −8 ). This was comparable to findings from traditional observational studies (prevalence odds ratio 0.73, 0.68 to 0.78; incidence odds ratio 0.80, 0.76 to 0.83). Sensitivity analyses were consistent with a causal interpretation in which major bias from genetic pleiotropy was unlikely, although this remains an untestable possibility. Genetic predisposition towards longer education was additionally associated with less smoking, lower body mass index, and a favourable blood lipid profile. Conclusions  This mendelian randomisation study found support for the hypothesis that low education is a causal risk factor in the development of coronary heart disease. Potential mechanisms could include smoking, body mass index, and blood lipids. In conjunction with the results from studies with other designs, these findings suggest that increasing education may result in substantial health benefits.